Media art in healthcare environments: enhancing student’s well-being and mental health / Raja Eda Shabina Raja Raimie, Mohammad Kamal Sabran and Nur Zaidi Azraai - Raja Raimie, Raja Eda Shabina; Sabran, Mohammad Kamal; Azraai, Nur Zaidi (Faculty of Art and Design, 2024)
New media art refers to works of art that have been developed or created through the combination of art and technology. New media art encompasses any contemporary art forms created, edited, or transmitted using new media technology. It includes digital, interactive, online, virtual, video, sound, and artworks made using robotics, video games, biotechnology, 3D printing, and computer animation. As a result, many studies have been conducted on the use of arts to promote a balanced way of life and the value of art in the healthcare setting, however, a lack of study on media arts as an art-based intervention in the healthcare environment. Therefore, the purpose of this research is to identify the existing elements and characteristics of the artworks in the healthcare environment and propose a prototype media art as a new art-based intervention to enhance a pleasant healthcare environment and potentially promote well-being and mental health among students in the institutional healthcare environment. This is qualitative research involving interviews with doctors and experts in fields and observation in Pusat Sejahtera Universiti Sains Malaysia, Pulau Pinang. The semi-structured interview and observation will be recorded through an audio-video recording system. As a result, this research will develop a prototype of media art that will be produced using a combination of art and technology. These include interactive art, sound art, visual, and computer art. This prototype will give students, visitors, and staff in healthcare a good impact and enjoyable experience in healthcare environments that may be undergoing stress while waiting for the treatments or after the treatment. This research's significance is beneficial to academia, the institution's healthcare environment in Malaysia, and students' well-being and mental health. As mentioned by the Director-General of Health, Datuk Dr Noor Hisham Abdullah, the future healthcare facility design goals are to create a healing environment, including art and hospitality.